2009
DOI: 10.1093/nar/gkp578
|View full text |Cite
|
Sign up to set email alerts
|

A fast and efficient translational control system for conditional expression of yeast genes

Abstract: A new artificial regulatory system for essential genes in yeast is described. It prevents translation of target mRNAs upon tetracycline (tc) binding to aptamers introduced into their 5′UTRs. Exploiting direct RNA–ligand interaction renders auxiliary protein factors unnecessary. Therefore, our approach is strain independent and not susceptible to interferences by heterologous expressed regulatory proteins. We use a simple PCR-based strategy, which allows easy tagging of any target gene and the level of gene exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
80
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(81 citation statements)
references
References 31 publications
1
80
0
Order By: Relevance
“…In this method, one measures, during a chase, the ratio of a test protein to a long-lived reference protein, the mouse dihydrofolate reductase (DHFR). The reference protein and test proteins were coexpressed on a low-copy plasmid from two identical P TDH3 promoters containing additional DNA elements developed by others (53). Once transcribed into an mRNA, these elements form 5′-RNA aptamers that can bind to tetracycline (Tc), thereby repressing translation of that mRNA in cis (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In this method, one measures, during a chase, the ratio of a test protein to a long-lived reference protein, the mouse dihydrofolate reductase (DHFR). The reference protein and test proteins were coexpressed on a low-copy plasmid from two identical P TDH3 promoters containing additional DNA elements developed by others (53). Once transcribed into an mRNA, these elements form 5′-RNA aptamers that can bind to tetracycline (Tc), thereby repressing translation of that mRNA in cis (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Both aptamers contain two asymmetrical internal loops that are not well ordered in the free RNA, but fold into a compact structure upon ligand binding, with one nucleotide capping the binding pocket. Evidence for a dynamic equilibrium of an ''inactive'' and an ''active'' state was provided for a theophylline-binding RNA aptamer (Latham et al 2009). Their results indicated that the RNA utilize a conformational selection mechanism for binding theophylline like other RNAs with conformationally heterogeneous free states, such as the aptamer domains in RNA riboswitches binding their ligands.…”
Section: Discussionmentioning
confidence: 99%
“…The tetracycline (Tc)-binding aptamer investigated in the present work has been used as an RNA switch for conditional gene expression in yeast, either inhibiting translation initiation (Suess et al 2003;Kötter et al 2009) or pre-mRNA splicing (Weigand and Suess 2007). The ligand Tc inhibits prokaryotic translation (Epe et al 1987;Spahn and Prescott 1996) and is used as a therapeutic agent of low toxicity .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the reporter gene in use seems to have an impact on the result as well. Fowler et al 40 and K€ otter et al 41 observed that the insertion of secondary structure elements in the 5 0 -UTR of a GFP gene can lead to a reduction in gene expression and, consequently, fluorescence intensity. Obviously, some of the riboswitch elements provoke a similar reduction.…”
Section: Increasing the Activation Ratio By Tandem And Tridem Constructsmentioning
confidence: 99%